2009
DOI: 10.1038/nrcardio.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the cardiovascular effect of sex hormones

Abstract: The higher incidence of cardiovascular disease in men than in women of similar age, and the menopause-associated increase in cardiovascular disease in women, has led to speculation that gender-related differences in sex hormones have a key role in the development and evolution of cardiovascular disease. Compelling data have indicated that sex differences in vascular biology are determined not only by gender-related differences in sex steroid levels, but also by gender-specific tissue and cellular differences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
201
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(209 citation statements)
references
References 145 publications
(145 reference statements)
5
201
1
2
Order By: Relevance
“…The evidence regarding the effects of endogenous testosterone on men's health has been mixed (Alexandersen et al 1996;Vitale et al 2009;Araujo et al 2011;Ruige et al 2011;Schooling 2015). Although some studies have reported negative associations between low testosterone levels and the risk of ischemic stroke and of all-cause, CVD, and cancer mortality; the question of whether these associations are causal, or whether testosterone is an important biomarker of overall male health, has yet to be fully investigated (Haring et al 2010;Holmegard et al 2016).…”
Section: Effects Of Testosteronementioning
confidence: 99%
“…The evidence regarding the effects of endogenous testosterone on men's health has been mixed (Alexandersen et al 1996;Vitale et al 2009;Araujo et al 2011;Ruige et al 2011;Schooling 2015). Although some studies have reported negative associations between low testosterone levels and the risk of ischemic stroke and of all-cause, CVD, and cancer mortality; the question of whether these associations are causal, or whether testosterone is an important biomarker of overall male health, has yet to be fully investigated (Haring et al 2010;Holmegard et al 2016).…”
Section: Effects Of Testosteronementioning
confidence: 99%
“…These circulating cells may stimulate reciprocal immune sensitization, resulting in the generation of mHAg-specific cytotoxic T lymphocytes (CTLs). 6 For example, this phenomenon accounts for the increased risk of immune complications and transplantationrelated mortality, observed when a parous female is used as allo-HSCT donor for a male recipient. 7 In their article in this issue of Blood, van Halteren and colleagues provide sound evidence that mHAg-specific CD8 ϩ regulatory T cells (T regs ) can also emerge during pregnancy and persist for many years.…”
Section: Franco Locatelli University Of Paviamentioning
confidence: 99%
“…As one example, it is well established that premenopausal women have lower rates of cardiovascular disease compared with men, although those rates increase after menopause when estrogen levels are lower, coinciding with lower telomere lengths in hematopoietic cells. 5,6 Could stem/progenitor cells of the vascular system also be dependent on estrogen to activate TERT, thereby enhancing cell lifespan, survival, and proliferation? Many similar provocative questions regarding aging and cancer arise from the studies by Calado et al, an attribute ascribed to groundbreaking scientific investigation.…”
Section: Org Frommentioning
confidence: 99%
“…Central adiposity, is associated with insulin resistance, hyperinsulinaemia, type-II diabetes and the metabolic syndrome, and these are all linked to reduced testosterone concentrations in men [32,33].…”
Section: Cardioprotective Effects Of Testosteronementioning
confidence: 99%